HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN PERENCANAAN KARIR SISWA KELAS XI SMK NU 02 ROWOSARI KABUPATEN KENDAL: HUBUNGAN DUKUNGAN SOSIAL ORANG TUA DENGAN PERENCANAAN KARIR SISWA KELAS XI SMK NU 02 ROWOSARI KABUPATEN KENDAL - Awaliyah, Rizka Khoirotul (MEDI KONS: Jurnal Prodi Bimbingan dan Konseling UNISRI Surakarta, 2023)
The purpose of this study was to determine the relationship between career planning and parental support for class XI Marketing SMK NU 02 Rowosari. This research is a type of correlational quantitative research conducted in the odd semester of the 2022/2023 academic year at SMK NU 02 Rowosari Kendal. The population in this study was all students of class XI Marketing. The sampling technique used proportional random sampling, as many as 30 students were sampled. The instrument used is a Likert scale, the analytical technique used is the product moment. the results of the hypothesis test in the product moment correlation test obtained r count < r table 0.576 < 0.361 with a significance value of 0.001 < 0.005, which means that it can be concluded that the two variables are correlated. the variable is 0.576, Ha is accepted at a significant level of 5% and Ho is rejected with a coefficient of determination of 33%, based on these results that parental social support contributes to career planning by 33% while 67% is influenced by other factors. Keywords: Parental social support, career planning